Seasonal variation of ambulatory blood pressure in Chinese hypertensive adolescents - Zhou, Yi; Zhao, Lin; Meng, Xu; Cai, Qiu-Jing; Zhao, Xiao-Lei; Zhou, Xian-Liang; Hu, Ai-Hua (Frontiers in Pediatrics, 2022)
Background: Blood pressure (BP) exhibits seasonal variation with lower levels at higher ambient temperatures and vice versa. This phenomenon affects both sexes and all age groups. So far, only a few researches have investigated this condition in adolescents and none of them were based on hypertensive population or applied ambulatory blood pressure monitor (ABPM) . Therefore, we carried out the first study which used ABPM to record the seasonal variation of blood pressure in hypertensive adolescents. Methods: From March 2018 to February 2019, 649 reports from hypertensive adolescents between 13 to 17 years who were referred to wear an ABPM device in Beijing and Baoding were extracted. Seasonal change in ambulatory BP value, dipping status and prevalence of different BP phenotypes were analyzed and compared. Results: Mean age of participants was 14.9±1.5 years and 65.8 % of them were boy. 75% of participants met the criteria of overweight or obesity. From summer to winter, average 24-hour, day-time and night-time BP showed significant rise, which was 9.8/2.8 mm Hg, 9.8/3.0mmHg and 10.9/3.4mmHg respectively. This seasonal effect on BP was not dependent on obesity degree. In addition, higher prevalence of non-dippers and risers existed in winter while white coat hypertension (WCH) was more frequent in warmer seasons. Conclusion: Hypertensive adolescents showed evident seasonal change in their ABPM results, which was featured by elevated BP level and more frequent abnormal dipping patterns in winter. On the contrary, higher prevalence of white coat hypertension was found in warmer seasons. Physicians should take seasonal variation into consideration when managing adolescent hypertension.